2017
DOI: 10.1115/1.4037370
|View full text |Cite
|
Sign up to set email alerts
|

Biofuel Emulsifier Using High-Velocity Impinging Flows and Singularities in Microchannels

Abstract: The objective of this experimental work is to design an original microfluidic mixer for continuous emulsification of small fractions of water in a lipid phase. This system is aimed to be integrated on-line in the process so as to avoid the use of a surfactant. The currently targeted application is a better combustion of water-supplemented alternative biofuels in boilers, turbines, or internal combustion engines in general. Therefore, mean size of droplets of water in the emulsion should be 5–10 μm, and the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The finely dispersed droplets in W/O emulsion are consequently produced in the emulsion. Further modifications were made by placing 90° bend at outlet channels (Belkadi et al 2018) or arranging two impinging microsystems in series (Belkadi et al 2016) in order to produce emulsified biofuel with finer water dispersed droplets. Most recently, Ji et al (2020) reported oil-in-water emulsification process in this microsystem by characterizing the flow patterns and droplet size, emphasizing the advantage of two jets impinging configuration in the microchannel on transporting great kinetic energy to disrupt dispersed phase fluids.…”
Section: Drop Dynamics In Microfluidic Emulsifiermentioning
confidence: 99%
“…The finely dispersed droplets in W/O emulsion are consequently produced in the emulsion. Further modifications were made by placing 90° bend at outlet channels (Belkadi et al 2018) or arranging two impinging microsystems in series (Belkadi et al 2016) in order to produce emulsified biofuel with finer water dispersed droplets. Most recently, Ji et al (2020) reported oil-in-water emulsification process in this microsystem by characterizing the flow patterns and droplet size, emphasizing the advantage of two jets impinging configuration in the microchannel on transporting great kinetic energy to disrupt dispersed phase fluids.…”
Section: Drop Dynamics In Microfluidic Emulsifiermentioning
confidence: 99%
“…2(d). These bends are intended to enhance the breaking-up of droplets (Belkadi et al 2018). It has to be noted that previous works have led to the current design of the asymmetric system.…”
Section: Microchannelsmentioning
confidence: 99%
“…It has to be noted that previous works have led to the current design of the asymmetric system. For example, the effect of the number of bends (Bellettre et al 2017) and the length of the outlet channels (Belkadi et al 2018) have been studied. It has been observed that the length of the outlet channels should be selected depending on the viscosity ratio of the fluids.…”
Section: Microchannelsmentioning
confidence: 99%
“…Micro-channels transport phenomena are used in a wide spectrum of design modern energy systems and applications by chemical engineers, such as biofuels emulsifying agents [1], exchangers of heat [2], thermoelectric power technology [3], collectors of solar energy [4], processing of polymers [5], design of the condensers [6], the propulsion systems of the rocket [7]. Other utilizes include naphtha redesigning and the systems of sustainable hydrogen fuel.…”
Section: Introductionmentioning
confidence: 99%